TREATMENT WITH SILDENAFIL CITRATE IN RENAL TRANSPLANT PATIENTS WITH ERECTILE DYSFUNCTION - REHMAN , KU; MANAN , FE; ULLAH , I; MINALLAH , H (Biological and Clinical Sciences Research Journal, 2024)
Erectile dysfunction (ED) is a prevalent and distressing condition among renal transplant patients, often stemming from multifactorial causes such as medication side effects, psychological factors, and vascular complications associated with end-stage renal disease (ESRD) and transplantation. The basic aim of the study is to find the treatment with sildenafil citrate in renal transplant patients with erectile dysfunction (ED). This prospective observational study was conducted at the Institute of Kidney Disease Peshawar from 2017 to 2023. A total of 240 participants were recruited using convenience sampling methods. All male patients aged 18 years or older who had undergone renal transplantation and reported persistent ED for a duration of at least six months post-transplantation. Patients who use nitrate medications, severe cardiovascular disease, and uncontrolled hypertension were excluded from the study. Data were collected from 240 patients. The mean age of the patients was 52 ± 8.01 years and the mean duration of the transplant was 5.1 ± 3.2 years. Almost 70% of patients were suffering from hypertension, 45% from DM, and 30% from CVD. The mean level of serum creatinine was 1.5 ± 0.3 mg/dl and the mean GFR was 60 ± 10mL/min/1.73m². The assessment at baseline revealed an IIEF erectile function score of 12.5, which significantly improved to 20.2 at the 12-week follow-up, indicating a notable enhancement in erectile function among participants. Moreover, the frequency of successful intercourse also exhibited a positive change, with participants reporting an increase from 1-2 times per month at baseline to 3-4 times per month at the 12-week. It is concluded that sildenafil citrate demonstrates significant efficacy in improving erectile function and sexual satisfaction among renal transplant patients with erectile dysfunction.